Mutations in the kinesin-like protein Eg5 disrupting localization to the mitotic spindle. - Sawin, K E (1995)
Eg5, a member of the bimC subfamily of kinesin-like microtubule motor proteins, localizes to spindle microtubules in mitosis but not to interphase microtubules. We investigated the molecular basis for spindle localization by transient transfection of Xenopus A6 cells with myc-tagged derivatives of Eg5. Expressed at constitutively high levels from a cytomegalovirus promoter, mycEg5 protein is cytoplasmic throughout interphase, begins to bind microtubules in early prophase, and remains localized to spindle and/or midbody microtubules through mitosis to the end of telophase. Both N- and C-terminal regions of Eg5 are required for this cell-cycle-regulated targeting. Eg5 also contains within its C-terminal domain a sequence conserved among bimC subfamily proteins that includes a potential p34cdc2 phosphorylation site. We show that mutation of a single threonine (T937) within this site to nonphosphorylatable alanine abolishes localization of the mutant protein to the spindle, whereas mutation of T937 to serine preserves spindle localization. We hypothesize that phosphorylation of Eg5 may regulate its localization to the spindle in the cell cycle.